PENETAPAN KADAR FENOLIK SERTA UJI AKTIVITAS ANTIOKSIDAN EKSTRAK DAN FRAKSI BATANG BAJAKAH KALALAWIT (Uncaria gambir Roxb) DENGAN METODE FRAP - Siti Nur Indriyah; Desy Ayu Irma Permatasari; Kharisma Jayak Pratama (Institut Nalanda, 2023)
Antioxidants are compounds prevent oxidative damage by stabilizing free radicals by donating electrons. Phenolics are compounds that can be used as antioxidants because they can counteract free radicals. This study aims to determine the total phenolic content and antioxidant activity of the extract and fraction of the kalalawit (Uncaria gambir Roxb) stem. Extract preparation by maceration using 96% ethanol solvent. Testing for phenolic content with the Folin Ciocalteu method using UV-Vis spectrophotometry on extracts. Antioxidant activity test using the FRAP method on extracts with concentrations of 80, 90, 100, 110, and 120 ppm. The test results showed that the extract of the bajakah kalalawit stem (Uncaria gambir Roxb) had a phenolic content of 31.734 mg GAE/gr sample, there was antioxidant activity in the extract and fraction of the stem of the kalalawit (Uncaria gambir Roxb) indicated by the formation of a purplish blue color when reacted with FRAP solution , and the IC50 value of the ethanol extract was 29.842 ppm which was in the very strong category, water fraction was 39.865 ppm which was in the very strong category, n-hexane fraction was 75.319 ppm which was in the strong category and ethyl fraction was 12.572 ppm which was very strong.